2009
DOI: 10.1002/mc.20523
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at p53, p73, and MDM2 loci modulate the risk of tobacco associated leukoplakia and oral cancer

Abstract: Polymorphisms at loci controlling cellular processes such as cell cycle, DNA repair, and apoptosis may modulate the risk of cancer. We examined the association of two linked polymorphisms (G4C14-A4T14) at p73 and one polymorphism (309G > T) at MDM2 promoter with the risk of leukoplakia and oral cancer. The p73 and MDM2 genotypes were determined in 197 leukoplakia patients, 310 oral cancer patients and in 348 healthy control subjects. The p73 GC/AT genotype increased the risk of leukoplakia (OR = 1.6, 95% CI = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Five independent studies investigating the genetic effects of MDM2 SNP309T>G on OSCC risk (9-13) were included in this meta-analysis. Among these, 1 study demonstrated that MDM2 SNP309T>G was associated with a reduced risk of OSCC (13), while the remaining 4 studies provided no evidence of an association between this SNP and OSCC risk (9)(10)(11)(12). A meta-analysis of the 5 studies, including 1,369 cases and 2,167 controls, was performed to investigate the overall effects of MDM2 SNP309 on OSCC risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five independent studies investigating the genetic effects of MDM2 SNP309T>G on OSCC risk (9-13) were included in this meta-analysis. Among these, 1 study demonstrated that MDM2 SNP309T>G was associated with a reduced risk of OSCC (13), while the remaining 4 studies provided no evidence of an association between this SNP and OSCC risk (9)(10)(11)(12). A meta-analysis of the 5 studies, including 1,369 cases and 2,167 controls, was performed to investigate the overall effects of MDM2 SNP309 on OSCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous previous studies have investigated the association between MDM2 SNP309 and OSCC risk (9)(10)(11)(12)(13)(14)(15). However, the results remain inconsistent and ambiguous, partly due to the relatively small sample sizes of the independent studies and sampling effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one recent meta-analysis also detected no evidence of a significant association between the TP53 Arg72Pro polymorphism and risk of oral cancer (Zhuo et al, 2009b), and another meta-analysis observed a significant association of the TP53 Arg72Pro polymorphism with nasopharyngeal cancer susceptibility (Zhuo et al, 2009a), which are all consistent with our results. Nevertheless, three more eligible articles related to oral cancer (Tandle et al, 2001;Kietthubthew et al, 2003;Misra et al, 2009) and one more eligible article related to nasopharyngeal cancer (Golovleva et al, 1997) were included in our meta-analysis that were not included in the two previous meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al (2002) analyzed oral, pharyngeal, and laryngeal cancer specifically, whereas Ji et al (2008) and Chen et al (2008) studied oropharyngeal cancer as well as oral cancer. Overall, a total of 27 studies consisting of 3966 HNCs cases and 4387 controls were included in our meta-analysis (Yung et al, 1997;Golovleva et al, 1997;McWilliams et al, 2000;Hamel et al, 2000;Summersgill et al, 2000;Tandle et al, 2001;Sourvinos et al, 2001;Nagpal et al, 2002;Shen et al, 2002;Tsai et al, 2002;Tiwawech et al, 2003;Kietthubthew et al, 2003;Katiyar et al, 2003;Scheckenbach et al, 2004;Cortezzi et al, 2004;Hsieh et al, 2005;Sousa et al, 2006;Twu et al, 2006;Hadhri-Guiga et al, 2007;Perrone et al, 2007;Kuroda et al, 2007;Ji et al, 2008;Chen et al, 2007Chen et al, , 2008Lin et al, 2008;Tu et al, 2008;Misra et al, 2009) (Table 2). The genotype distribution of the TP53 Arg72Pro polymorphism is summarized in Table 3.…”
Section: Literature Search Screening and Data Collectionmentioning
confidence: 99%
“…Of these regulators, the murine double minute clone 2 (MDM2) proto-oncogene, an important negative regulator of the p53 gene, has become a point of interest (8). MDM2 is a major regulator of p53 function.…”
Section: Introductionmentioning
confidence: 99%